Clinical application of cervical shear wave elastography in predicting the risk of preterm delivery in DCDA twin pregnancy - Jimei Sun; Nan Li; Wei Jian; Dingya Cao; Junying Yang; Min Chen (BMC, 2022)
Abstract Background Limited studies have used cervical shear wave elastography (SWE) as a tool to investigate the predictive effect of cervical changes on preterm delivery (PTD) in twin pregnancy. This study is aimed to predict the risk of PTD by cervical SWE in dichorionic diamniotic (DCDA) twin pregnancy. Methods A total of 138 women with dichorionic diamniotic (DCDA) twins were included in this prospective study. The mean SWE value of the cervix was obtained from the inner, middle and outer regions of the anterior and posterior cervical lips using a transvaginal ultrasound transducer and measured consecutively across three different gestations (20-23+ 6 weeks, 24-27+ 6 weeks, and 28-32 weeks). Follow-up was performed on all subjects, and we compared the mean SWE value between the PTD and term delivery (TD) groups. Results A total of 1656 cervical mean SWE data were collected for analysis. Among the 138 twin pregnant women, only 92 women completed the three elastography examinations; PTD occurred in 58.7% (54/92), and TD in 41.3% (38/92). The mean (SD) maternal age was 33.1 ± 4.1 years, and the mean (SD) body mass index was 21.1 ± 2.6 kg/m2. As gestational age increased, the mean SWE value of each part of the cervix decreased. The cervical mean SWE value was lower in the preterm group than in the term group in all three gestations, except for the anterior cervical lip at 28-32 weeks. Receiver operating characteristics (ROC) curves showed the sensitivity of mean SWE value of the anterior cervical lip was 83.3% (95% CI, 70.7-92.1) with a specificity of 57.9% (95% CI, 40.8-73.7) for predicting PTD at a cutoff value of 7.94 kPa. The positive likelihood ratio (LR+) was 1.67 (95% CI, 1.19-2.34), and the negative likelihood ratio (LR-) was 0.33 (95% CI, 0.17-0.64). Conclusions There is a significant negative correlation between cervical stiffness and gestational age in DCDA twin pregnancy. SWE is a potential tool for assessing cervical stiffness and predicting PTD in DCDA twin pregnancy.